Ayurvedic Management of Huntington’s Chorea (Tandava Roga): A Case of Rare Genetic Condition - Mrunal Sunil Bole; Sourabh Deshmukh; Trupti Thakre (Journal of Clinical and Diagnostic Research)
Huntington’s chorea is a rare genetic neurodegenerative disorder. It is an inherited disease that manifests as motor, cognitive, and psychiatric abnormalities. The disease is caused by a genetic mutation involving Cytosine-Adenine-Guanine (CAG) repeat expansion on chromosome 4. According to Ayurveda, Huntington’s chorea can be correlated with Tandava Roga, as mentioned in the Sharangdhara Samhita. A 50-year-old male patient presented to the Outpatient Department of Kayachikitsa, diagnosed with Huntington’s chorea based on positive family history, molecular genetic analysis, and chief complaints of abnormal involuntary movements. The Ayurvedic treatment approach was classically based on Shodhana and Shamana. The principles used included Balya (strengthening), Vatahara, Rasayana, and nerve-stimulating actions. The patient underwent Shodhana with medicated enema (basti) for strotoshodhana (detoxification of body channels), along with other procedures such as Shashti Shali Pind Swedan, Nasya, Shirodhara, and Shirotalam for three sittings. The same treatment was followed, with the patient returning for Panchakarma procedures every two months (three sittings). Along with Shodhana, some Shamana medications were advised during the course of treatment for six months, accompanied by Pathya sevan. Assessment was done using the Abnormal Involuntary Movement Scale (AIMS), which showed marked improvement, with the score reducing from 33 to 11 over six months of treatment. The Ayurvedic approach can help improve the condition of patients with Huntington’s chorea. Similar treatments can be utilised in such patients to study their efficacy in varied individual cases.